AN ANALYSIS OF THE STUDENT'S DIFFICULTIES IN DEVELOPING IDEAS IN A PARAGRAPH - Miftah Rizkina; Sukri Adani (Nusantara Hasana Journal, 2024)
This study analyzes the difficulties experienced by second-semester students at STKIP Muhammadiyah Aceh Barat Daya in developing ideas in writing paragraphs. This study uses a qualitative case study approach with semi-structured interviews as the main instrument, with 15 students. The results of the study show that students often have difficulties in coherently arranging ideas, choosing the right vocabulary, and understanding correct grammar. The main factors that cause this difficulty are a lack of in-depth understanding of the topic being written, limited time in completing the task, as well as the challenge of connecting ideas logically in paragraphs. In addition, the results of the study revealed that the teaching methods applied by lecturers, such as giving real examples and constructive feedback, help students in improving their writing skills. However, students still face obstacles in applying the theories they have learned into effective writing practices. The study also found that strategies such as brainstorming, mind mapping, and peer discussions helped students develop their ideas before starting the formal writing process. Overall, this study emphasizes the importance of a deep understanding of the topic, adequate time allocation, and effective pedagogical support in helping students overcome difficulties in developing ideas in paragraph writing. These findings provide valuable insights for educators in designing more effective teaching strategies to improve students' writing skills.